Prestebol og prestegjeld på landet i Stavanger bispedømme i middelalderen - Stylegar, Frans-Arne; Brendalsmo, Jan (Hikuin, 2006)
Vicarage and parish in Stavanger diocese in the Middle Ages By Frans-Arne Stylegar and Jan Brendalsmo In historical research the vicarages in Norway are usually believed to have been common in the 14th century, and to have been established by the owner of the church farm. Our research indicates that while vicarages (prestebol) did exist in the 14th century, the majority of priests lived either in separate rooms or separate buildings at the church farm, and that several of them probably were employed on a yearly basis, as were ordinary farm workers. Only a minority of priests were owner-occupiers, and it was most likely a common occurrence that the priests’ holdings lay in between strips belonging to other farmers (i.e. a runrig system). For different kinds of reasons a structural change in the Church’s organisation occurred at the end of the 14th and in the 15th century, in the sense that parishes were organised, the boundaries of the existing vicarages were regularised and new vicarages established at all churches, each with a resident priest, and the land rent was allocated to the church’s fabrica, i.e. to the church building and its maintenance, and to priest’s mensa, i.e. to defraying the expenses of the priest. The Plague in 1348-50 led to a reduction both in the number of priests and in the level of ecclesiastical revenues, and this contributed to a reorganisation of the Church’s holdings. Furthers reasons for the late-medieval reorganisation was the fact that the Church’s leaders now had a firmer grip on pastoral care in Norway, and that the owners of the private churches had changed their attitutes regarding the ownership of churches and priests. Still, it is primarily in the late 15th and early 16th century that the bishops and, later, the king’s officials took action and established separate farms for the priests, i.e. vicarages of a type known in later centuries.